2022
DOI: 10.1124/jpet.121.001251
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Improves the MicroRNA Signature of Endothelial Dysfunction in Patients with Heart Failure with Preserved Ejection Fraction and Diabetes

Abstract: Endothelial dysfunction represents a key mechanism underlying heart failure with preserved ejection fraction (HFpEF), diabetes mellitus (DM), and frailty. However, reliable biomarkers to monitor endothelial dysfunction in these patients are lacking. In this study, we evaluated the expression of a panel of circulating microRNAs (miRNAs, miRs) involved in the regulation of endothelial function in frail older adults with HFpEF and DM that were treated for 3 months with empagliflozin, metformin, or insulin. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 110 publications
0
34
0
2
Order By: Relevance
“…Empagliflozin was the first to be proved to improve HFpEF by a randomized controlled trial with sufficient statistical efficacy. Some molecular mechanisms proposed that empagliflozin could improve the specific circulating microRNA to regulate the endothelial function significantly and empagliflozin could reduce inflammatory and oxidative stress in HFpEF to decrease pathological cardiomyocyte stiffness by inhibiting NHE1 (Na+/H+ exchanger 1), which supported the wide use of empagliflozin in HFpEF (37)(38)(39). However, over 86% of HFpEF were using ACE-I/ARBs, 80% were using beta-blockers, and over 24% were using spironolactone in reality (7), which increased the burden of treating HFpEF to some extent.…”
Section: Discussionmentioning
confidence: 97%
“…Empagliflozin was the first to be proved to improve HFpEF by a randomized controlled trial with sufficient statistical efficacy. Some molecular mechanisms proposed that empagliflozin could improve the specific circulating microRNA to regulate the endothelial function significantly and empagliflozin could reduce inflammatory and oxidative stress in HFpEF to decrease pathological cardiomyocyte stiffness by inhibiting NHE1 (Na+/H+ exchanger 1), which supported the wide use of empagliflozin in HFpEF (37)(38)(39). However, over 86% of HFpEF were using ACE-I/ARBs, 80% were using beta-blockers, and over 24% were using spironolactone in reality (7), which increased the burden of treating HFpEF to some extent.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, diabetes leads to a higher risk of cardiovascular complications and functional and physical impairment driving adverse outcomes (Fadini and Avogaro, 2010;Prattichizzo et al, 2018;Yun et al, 2018;Jarvie et al, 2019;Yu et al, 2019;Gulsin et al, 2020). microRNAs (miRNAs) are small non-coding RNAs that act as post-transcriptional gene regulators (Ambros, 2004;Krol et al, 2010;Santulli, 2015;Ferrante and Conti, 2017;Fridrichova and Zmetakova, 2019;Stavast and Erkeland, 2019;Mone et al, 2021b;Mone et al, Forthcoming 2022c); miRNAs exert their activity in many biological processes and have been proposed as biomarkers and therapeutic strategies (Creemers et al, 2012;Wronska et al, 2015;Barwari et al, 2016;Chen et al, 2018;Wong et al, 2018;Mone et al, 2021b;Fonseca et al, 2021;Mone et al, Forthcoming 2022c). Many miRNAs have been associated to mitochondrial dysfunction, inflammation, and oxidative stress and their concentration may vary in physiological conditions (Zhang et al, 2014;Hathaway et al, 2018;Wei et al, 2018;Rusanova et al, 2019;Song et al, 2019;Gambardella et al, Forthcoming 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A different, recently proposed biomarker of aging trajectories is miR-21, which is increased during aging and in age-related diseases [ 96 ]. Of note, a 3-month treatment with empagliflozin was recently reported to restore the blood circulating quantities of this miRNA in frail older adults with heart failure and diabetes mellitus; the study also demonstrated that this effect was specific for the SGLT-2i, compared with treatment with insulin, or also metformin in the same patients [ 97 ].…”
Section: Effect Of Sglt-2i On Biomarkers Of Aging and Inflammaging In...mentioning
confidence: 99%